Behind Disaster Management: Resiliency in Cultural Configuration - Bhattarai, Raj Kumar (Journal of Business and Social Sciences, 2018)
The paper discovers the worth of a resilient culture in the course of disaster management following 2015’s Nepal Earthquake. An empirical investigation into the activities of rescues, rescuers, government authorities, humanitarian agencies, and civil societies indicates that the effectiveness of rescue, relief, recovery, and reconstruction activities are influenced by their cultural resiliency. The discovery process involved field visits, personal observation and experience, interviews, literature review and discourse analysis as well as interpretation. The study concentrated on the issues concerning the areas of rescue operations, logistics, information sharing, supply chains, shelter management, relief packages distribution, actors’ coordination, and socio-cultural immunity and elasticity to the crisis conditions. This paper draws a conclusion that resilience in cultural configuration enhances effectiveness in the process of disaster management.